A novel supramolecular self-assembling hybrid system for visible-light-driven overall water splitting. (6th September 2022) - Zuo, Minzan; Qian, Weirui; Wang, Kaiya; Wang, Leyong; Hu, Xiao-Yu
Abstract : A hybrid supramolecular system containing redox compartments has been successfully developed for visible-light-driven overall water splitting in the ambient environment. Abstract : A hybrid supramolecular system for visible-light-driven overall water splitting has been successfully developed. The material is fabricated from a host–guest complex formed between a cyclodextrin-modified sensitizer and a phenyl-modified catalyst, serving as the oxidation compartment. Meanwhile, the reduction compartment is formed by electrostatic self-assembly of reduced graphene oxide and protonated graphitic C3 N4, as well as passive loading of 0.5 wt% Pt. As a result, the photocatalytic overall water splitting can be realized in the ambient environment in the presence of only a sacrificial reductant, but with no need for a sacrificial oxidant. This is mainly because the reduced graphene oxide can act as an electron transporter to facilitate effective charge transfer from the oxidation compartment to reduction compartment. This work highlights an appealing approach of supramolecular self-assembly for conversion of solar energy into chemical fuels.